Existential Issues of Human Existence in the Poetry of Shakarim Kudayberdiuly and Eduard Mizhit - Umbetayev, Shyngys A.; Temirbolat, Alua B. (The New Research of Tuva, 2026)
The article analyzes the poetry of two authors from Turkic-speaking peoples, the Kazakh writer Shakarim Kudayberdiuly and the Tuvan poet Eduard Mizhit, in the context of Irvin Yalom’s existential psychologism and his concept of the “four givens of existence.” The study aims to identify the ways in which fundamental categories of human existence — freedom of choice, loneliness, death, and the search for the meaning of life in artistic creativity and in the system of moral values — are conceptualized in the works of the Kazakh and Tuvan authors. Their works are examined in terms of their philosophical and aesthetic views and the ethnocultural traditions within which their literary legacy was formed and developed. The article compares poetic strategies for comprehending the fundamental givens of existence, focusing on nationally conditioned forms of expressing ultimate personal experience in the authors’ works, and reveals typological similarities and differences in the interpretation of existential problems in their poetry. The study establishes that existential psychologism is a key element in the poets’ works. In the writings of the authors considered, there is a commonality of philosophical problematics alongside differences in the artistic models of its expression, which are shaped by the historical experience and cultural traditions within which their aesthetic views and worldview were formed. In Sh. Kudayberdiuly’s lyric poetry, the fundamental givens are interpreted primarily through ethical problematics, moral choice, and the idea of spiritual self-perfection of the individual. In the poetry of E. Mizhit, introspection, experience of the absurdity of existence, ontological anxiety, and motifs of loneliness predominate, bringing his works closer to the psychological interpretation of existential experience.